2018
DOI: 10.1111/pce.13205
|View full text |Cite
|
Sign up to set email alerts
|

Water relations of Calycanthus flowers: Hydraulic conductance, capacitance, and embolism resistance

Abstract: For most angiosperms, producing and maintaining flowers is critical to sexual reproduction, yet little is known about the physiological processes involved in maintaining flowers throughout anthesis. Among extant species, flowers of the genus Calycanthus have the highest hydraulic conductance and vein densities of species measured to date, yet they can wilt by late morning under hot conditions. Here, we combine diurnal measurements of gas exchange and water potential, pressure-volume relations, functional respo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 53 publications
5
55
1
Order By: Relevance
“…Mass flow through xylem cells is the only means by which sufficient water can be carried internally to support transpiring leaves. However, because rates of water supply and water loss from petals can be low Roddy & Dawson, 2012;Roddy et al, 2018), the phloem contribution of water might be a relatively larger fraction of the total water needed by the flower. Variation of water transport in flowers suggests that different species may employ different hydraulic conductance strategies to remain turgid and to maintain function during flowering (Chapotin et al, 2003;Feild et al, 2009;Roddy et al, 2018).…”
Section: Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…Mass flow through xylem cells is the only means by which sufficient water can be carried internally to support transpiring leaves. However, because rates of water supply and water loss from petals can be low Roddy & Dawson, 2012;Roddy et al, 2018), the phloem contribution of water might be a relatively larger fraction of the total water needed by the flower. Variation of water transport in flowers suggests that different species may employ different hydraulic conductance strategies to remain turgid and to maintain function during flowering (Chapotin et al, 2003;Feild et al, 2009;Roddy et al, 2018).…”
Section: Researchmentioning
confidence: 99%
“…However, because rates of water supply and water loss from petals can be low Roddy & Dawson, 2012;Roddy et al, 2018), the phloem contribution of water might be a relatively larger fraction of the total water needed by the flower. Variation of water transport in flowers suggests that different species may employ different hydraulic conductance strategies to remain turgid and to maintain function during flowering (Chapotin et al, 2003;Feild et al, 2009;Roddy et al, 2018). However, recent studies have suggested that flowers may be hydrated by xylem, at least in basal angiosperms (Chapotin et al, 2003;Roddy et al, 2018).…”
Section: Researchmentioning
confidence: 99%
See 3 more Smart Citations